Driving change in higher education: the role of dynamic capabilities in strengthening universities' third mission - Maribel Guerrero; Matthias Menter (Small Business Economics, 2024)
Abstract Universities play a crucial role in social, economic, and technological development. Over the last decades, higher education systems have experimented with multiple transformations due to social demands, socioeconomic paradigms, and external shakeouts. Even though teaching and research are still the core functions of universities, other activities are emerging within/beyond the universities' scope and boundaries to configure the “third mission.” Despite the increasing importance of universities' third mission, little is known about the role of dynamic capabilities underpinning the configuration of the third mission across higher education systems. Using a unique longitudinal dataset that captures the German higher education landscape from 2000 to 2016, we investigate the effect of dynamic teaching/research capabilities for achieving the third university mission (knowledge transfer and technology commercialization). Our results reveal tensions between complementary and substitution effects when pursuing universities' three missions (teaching, research, and knowledge transfer and technology commercialization), requiring university managers' and policymakers' strategic decisions. We provide implications for university managers and the university community as well as policymakers during the re-configuration process of becoming more entrepreneurial and innovative, highlighting the relevance of effectively managing universities' dynamic capabilities.
Additional information: I23;O31;O33
Keywords: 330; Third mission of universities; Knowledge transfer; Entrepreneurial universities; Ordinary capabilities; Dynamic capabilities; Strategic decision-making